PENGARUH METODE GAMIFIKASI BERBANTUAN KAHOOT TERHADAP KETERAMPILAN MEMBACA SISWA KELAS III PADA MATA PELAJARAN BAHASA INDONESIA DI SD - Sandrina Dwi Melany; Ahmad Syarif; Desy Rosmalinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of gamification method assisted by Kahoot on the reading comprehension skills of third-grade elementary school students in Bahasa Indonesia subject. The study employed a quantitative approach with a quasi-experimental design using a Pretest-Posttest Control Group Design. Subjects consisted of 42 students from SDN 100 Muara Bungo, divided into an experimental class (Class III C, n=21) and a control class (Class III A, n=21). The experimental class received gamification-based learning using Kahoot, while the control class used conventional methods. Data were collected through reading comprehension tests covering three indicators: finding explicit and implicit information, identifying story elements (characters, setting, events), and drawing conclusions. Validity was tested using Pearson Product Moment correlation, and reliability using Cronbach’s Alpha (α = 0.746). Data analysis included normality test (Shapiro-Wilk), homogeneity test (Levene’s Test), Independent Sample t-test, and N-Gain test. Results showed that the experimental class achieved a posttest mean of 81.10, significantly higher than the control class mean of 71.67. The Independent Sample t-test yielded a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between groups. The N-Gain score for the experimental class was 0.46 (medium category), compared to 0.18 (low category) for the control class. The study concludes that the gamification method assisted by Kahoot has a significant positive effect on the reading comprehension skills of third-grade elementary students.